2023
DOI: 10.1002/fes3.466
|View full text |Cite
|
Sign up to set email alerts
|

GmTNRP1, associated with rhizobial type‐III effector NopT, regulates nitrogenase activity in the nodules of soybean (Glycine max)

Abstract: Soybean is a rich source of protein and oil for humans. It forms a symbiotic association with rhizobia to fix atmospheric nitrogen for its growth and development.Rhizobial type-III effectors act as important signaling molecules in symbiosis.However, they are poorly studied. In this study, mutation of TtsI in Sinorhizobium fredii HH103 reduced nodule numbers and dry weights in SN14 (cultivated soybean) and ZYD00006 (wild soybean). Moreover, it reduced nitrogenase activity in SN14 but not in ZYD00006. Based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 84 publications
1
6
0
Order By: Relevance
“…T3Es can exert their functions when secreted into plants, whereupon host proteins can respond to or interact with these effectors. Both genetic and RNA-seq analyses have been utilized to identify the downstream response pathways and interacting proteins associated with these T3Es [21,24,57,58]. Here, RNA-seq analyses revealed that NopAA can induce substantial numbers of DEGs enriched in the MAPK pathway, in line with prior data related to rhizobia infection.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…T3Es can exert their functions when secreted into plants, whereupon host proteins can respond to or interact with these effectors. Both genetic and RNA-seq analyses have been utilized to identify the downstream response pathways and interacting proteins associated with these T3Es [21,24,57,58]. Here, RNA-seq analyses revealed that NopAA can induce substantial numbers of DEGs enriched in the MAPK pathway, in line with prior data related to rhizobia infection.…”
Section: Discussionsupporting
confidence: 77%
“…With the exception of the complete inhibition of Rj2-soybean nodulation in response to NopP in USDA122, there have not been any reports of any one T3E completely determining whether or not nodulation can occur [56]. In previous studies, our team has utilized HH103 T3E gene insertion mutants and a variety of soybean genetic resources to assess nodulation dynamics, revealing soybean varietyspecific effects of these T3Es [21,24,44]. Both NopAA and NopD were previously found to be likely contributors to the nodulation process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Analogous to NopL, NopT's transient expression in Nicotiana benthamiana results in leaf necrosis and elicits a hypersensitive response (HR) [29]. Additionally, NopT induction of GmTNRP1, an LRR-RK family protein at the cell membrane, serves to downregulate nitrogenase activity [30].…”
Section: Introductionmentioning
confidence: 99%